2022
DOI: 10.3390/app122312013
|View full text |Cite
|
Sign up to set email alerts
|

Time-Synchronized Microwave Cavity Resonance Spectroscopy and Laser Light Extinction Measurements as a Diagnostic for Dust Particle Size and Dust Density in a Low-Pressure Radio-Frequency Driven Nanodusty Plasma

Abstract: In a typical laboratory nanodusty plasma, nanometer-sized solid dust particles can be generated from the polymerization of reactive plasma species. The interplay between the plasma and the dust gives rise to behavior that is vastly different from that of pristine plasmas. Two of the key parameters in nanodusty plasma physics are, among other things, the dust particle size and the dust density. In this work, we introduce a novel method for the determination of these two quantities from the measurement of the fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 75 publications
(86 reference statements)
0
1
0
Order By: Relevance
“…75 Using this method for a proof of principle measurement, it was found that for our experimental conditions, we have grown dust particles with an expected radius of a ¼ 107 6 6 nm. This value is not only similar to the results of other experiments in the literature, 47,62,76 but also matched ex situ SEM measurements of the same sample quite well (a SEM ¼ 116 6 13 nm). Furthermore, we established that the charging timescale from the OML model is most sensitive to the input positive ion density.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…75 Using this method for a proof of principle measurement, it was found that for our experimental conditions, we have grown dust particles with an expected radius of a ¼ 107 6 6 nm. This value is not only similar to the results of other experiments in the literature, 47,62,76 but also matched ex situ SEM measurements of the same sample quite well (a SEM ¼ 116 6 13 nm). Furthermore, we established that the charging timescale from the OML model is most sensitive to the input positive ion density.…”
Section: Discussionsupporting
confidence: 91%
“…More recently, we presented a method for determining the dust particle size and the dust density based on the combination of laser light extinction and electron density measurements. 62 In this work, we present a novel method for determining the dust particle size, based on the detachment of electrons bound to the dust particles upon irradiation with pulsed ultraviolet (UV) laser light. We have experimentally measured the additional free electron density in the plasma after the laser pulse, from which we show that the dust particle size can be determined from the re-charging timescale.…”
Section: Introductionmentioning
confidence: 99%
“…Nigala Aikeremu et al adsorbed SARS-CoV-2 spike 1 protein using plasma-modified porous polymers [6]. Tim Donders et al measured dust particle size and dust density in low-pressure radio-frequency-driven nanodusty plasma using time-synchronized microwave cavity resonance spectroscopy and laser light extinction measurements [7]. Xucheng Wang et al studied the influence of gap width on temporal nonlinear behaviors in CO 2 DBD under Martian conditions [8].…”
Section: Editorial For a Special Issue On Plasma Technology And Its A...mentioning
confidence: 99%
“…The invasive extraction itself however is prone to destroying the particle-growing plasma (van-Wetering-hickup [6]), an extraction technique that minimizes the drawback of the particle extraction was presented recently [7]. Non-invasive, in-situ methods are based on extinction measurements [8], even combined with microwave cavity resonance spectroscopy [9], or on the analysis of the polarization state of light scattered by the particles [10]. These approaches, however, often rely on the knowledge of the particle's optical properties, most notably the refractive index [11].…”
Section: Introductionmentioning
confidence: 99%